Careful Choices in Low Temperature Ceramic Processing and Slow Hydration Kinetics Can Affect Proton Conduction in Ceria. (27th May 2021) - Simons, Philipp; Torres, Kierstin P.; Rupp, Jennifer L. M.
Abstract: Low‐temperature ceramic proton conductors such as ceria are important for applications ranging from sensors and resistive switches to new devices like implantable solid‐oxide glucose fuel cells. Spray pyrolysis offers a promising fabrication route for proton‐conducting ceria, with direct liquid‐to‐solid synthesis and control over crystallinity and grain size. To date, there are conflicting reports on ceria's proton conduction mechanism, particularly whether the interior contributes to proton conduction or transport occurs exclusively along a surface water layer. In this work, proton conductivity is observed in sprayed ceria thin films at 125 °C and below. Post‐annealed films exhibit higher conductivity than as‐deposited films of 3.3 × 10 −5 S cm −1 at 25 °C, which is comparable to previous reports and ascribed to the increase in crystallinity and grain size by post‐annealing. This indicates that the interior of ceria in fact contributes to proton conduction. Remarkably slow hydration kinetics of ceria are observed, with time‐dependent conductivity equilibrating to 9.53 × 10 −6 S cm −1 after up to 76 h. This implies kinetics may have suppressed proton conduction in previous studies, explaining the strong fluctuations in reports to date. Slow protonation kinetics must be considered when designing functional ceria ceramics, for example, in electrochemical bio‐energy conversion, sensing or neuromorphic computing. Abstract : The proton conductivity of ceria deposited via spray pyrolysis is studied. It is found that ceria shows remarkably slow hydration kinetics at the order of multiple days, indicating that slow kinetics may be a source of fluctuation of observed proton conductivity to date. Analyzing the effects of thermal annealing on proton conductivity indicates the ceria interior contributes to proton conduction.